2013
DOI: 10.4103/0974-8490.118828
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of Ficus religiosa leaves against isoniazid+rifampicin and paracetamol induced hepatotoxicity

Abstract: Background:The present study was designed to investigate the hepato protective effect of methanolic extract of Ficus religisoa L., Moraceae, on isoniazid-rifampicin and paracetamol induced hepatotoxicity in rats.Materials and Methods:Male Wistar albino rats were divided into six groups; group 1 served as a control received vehicle (Distilled water), group 2 served as a toxic control, received isoniazid-rifampicin (100 mg/ kg, i.p.) or paracetamol 200mg/kg, p.o in sterile water, groups 3, 4 and 5 received 100, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
1
9
0
2
Order By: Relevance
“…The effect of extract was comparable with a standard drug, Liv 52. The biochemical effects were further confirmed by histological results [95].…”
Section: Hepato- Nephro-and Dermato-protective Effectsmentioning
confidence: 59%
See 1 more Smart Citation
“…The effect of extract was comparable with a standard drug, Liv 52. The biochemical effects were further confirmed by histological results [95].…”
Section: Hepato- Nephro-and Dermato-protective Effectsmentioning
confidence: 59%
“…Orally administered dose ranged from 50-2000 mg/kg of extract did not produce any significant changes in the autonomic or behavior responses in rats [56].In acute oral toxicity studies, the Ficus religiosa extract treated rats were observed for mortality up to 48 hrs. There was no mortality or any signs of behavioral changes observed after oral administration of methanol extract up to 5000 mg/kg body weight [95].…”
Section: Toxicitymentioning
confidence: 84%
“…[ 35 ] Others include gastroprotective effects of N. officinale ,[ 36 ] antimicrobial effects of Aloe, Cleome , and Ipomoea , spp.,[ 36 37 38 ] and hepatoprotective effects of Ficus , Kalanchoe , Momordica , and Rhus spp. [ 39 40 41 42 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ficus religiosa L. (Moraceae) (Parameswari et al. 2013 ), Bacopa monnieri L. (Composite) (Evan et al. 2016 ), Tamarix gallica L. (Tamaricaceae) (Urfi et al.…”
Section: Drug-induced Liver Injuryunclassified